Anticancer and Antioxidant Activities of Methanolic Extract of Ziziphus Spina-Christi Leaves against Human Gastric Carcinoma Cells - Samir Abdulkarim Alharbi (Journal of Pharmacy and Bioallied Sciences)
Background: Ziziphus spina-christi (Rhamnaceae) is employed in Middle Eastern countries for the treatment of different diseases. Earlier reports revealed that it is cytotoxic to oral cancer cells. Objective: The current study determined the antioxidant activity and the anticancer potential of methanolic extract of Z. spina-christi against gastric carcinoma. Materials and Methods: LC-MS analysis was used to determine the different phytoconstituents predicted to be present in the extract. The effect of the Z. spina-christi leaf extract against human gastric carcinoma (AGS) cell lines was evaluated using MTT assay and cellular apoptosis techniques. A ferric-reducing antioxidant power assay was used to assess the antioxidant effect. Results and Conclusion: The LC-MS analysis revealed 24 phytoconstituents and Z. spina-christi extract was cytotoxic on AGS cells with an IC50 value of 125.1 μg/ml. Incubation of AGS cells with the extract decreased the percentage of live cells with a significant increase in late apoptotic phase and necrotic phase in the cellular apoptosis assay. The Z. spina-christi extract showed a potent antioxidant effect. The results show that Z. spina-christi extract possesses cytotoxic and antioxidant actions.